2016
DOI: 10.1109/tbme.2016.2579021
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Directed Interactions Between HRV and EEG Activity in Children With TLE

Abstract: In contrast to AR-based estimation of PDC CCM was able to reveal time-courses and frequency-selective views of nonlinear interactions for the further understanding of complex interactions between the epileptic network and the ANS in children with TLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 36 publications
7
64
0
Order By: Relevance
“…In a former study [16], we have shown that CCM is able to replicate defined directed interactions in simulated deterministic system and systems with a certain level of additive noise. The introduced moving window-based timevarying implementation of CCM is able to replicate correct directionality and (relative) strength of interactions also by using rather short window lengths.…”
Section: Results Of Investigations Of Bivariate Ccm Are Given In Figumentioning
confidence: 96%
See 3 more Smart Citations
“…In a former study [16], we have shown that CCM is able to replicate defined directed interactions in simulated deterministic system and systems with a certain level of additive noise. The introduced moving window-based timevarying implementation of CCM is able to replicate correct directionality and (relative) strength of interactions also by using rather short window lengths.…”
Section: Results Of Investigations Of Bivariate Ccm Are Given In Figumentioning
confidence: 96%
“…Practically, CCM X!Y and CCM Y!X are examined using data sets X = x(t) and Y = x(t) of increasing data length L (the so-called "library length"). Information about the basic algorithm for cross mapping of X by using M Y (CCM X!Y ) for each library length L (and CCM Y!X respectively) can be found in [16] and in the supplementary material of [13]. The following are the main steps: -generate "shadow manifold" M Y ; -find defined number of nearest neighbors at each time point t in M Y ;…”
Section: Convergent Cross Mapping (Ccm)mentioning
confidence: 99%
See 2 more Smart Citations
“…In literature CCM has been successful in revealing the existence of causality in non-linear physiological signals [8,11,13]; its performance has also been superior in comparison to linear Granger causality when applied on non-linear physiological signals [8]. With its advantage, it is expected to unearth complex directional interaction between SBP and EMG.…”
Section: Convergent Cross Mappingmentioning
confidence: 99%